2011
DOI: 10.2519/jospt.2011.3638
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relationship Between Back Muscle Endurance and Familial, Physical, Lifestyle, and Psychosocial Factors in Adolescents and Young Adults

Abstract: Low back pain (LBP) is currently the most prevalent and costly musculoskeletal pain disorder, with increasing incidence throughout adolescence. 59 Adolescent LBP has also been linked to LBP in adulthood. 6 Therefore, clinical strategies have been investigated to prevent and rehabilitate LBP, including addressing back muscle endurance (BME). This previous research has identified that BME, as determined by the Beiring-Sorenson test, is predictive of LBP in specific populations, 3,31 and that reduced BME is a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In a study conducted by Campbell et al, the results demonstrated that a significant correlation was found between spinal muscle activity and the percentage of fat tissue. They concluded that the percentage of fat tissue was a strong predictive index . Some mechanisms for this conclusion were individual deconditioning and an increased body mass index.…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted by Campbell et al, the results demonstrated that a significant correlation was found between spinal muscle activity and the percentage of fat tissue. They concluded that the percentage of fat tissue was a strong predictive index . Some mechanisms for this conclusion were individual deconditioning and an increased body mass index.…”
Section: Discussionmentioning
confidence: 93%
“…The test has moderate construct validity, with fatigue the most common reason reported for test termination [36]. The test required participants to lie prone, with their lower body supported on a plinth, and hold their trunk level with their lower body for as long as possible [37]. …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a growing body of research has linked static and dynamic nonneutral spinal postures with LBP, including populations of adolescents , adults (Dankaerts et al, 2009), adolescent rowers (Ng et al, 2008), and cyclists (Burnett et al, 2004). Furthermore, there is evidence that adopting end-range sagittal plane spinal positions results in reduced activity of the lumbopelvic stabilizing muscles, and is associated with poorer back muscle endurance (Campbell et al, 2011), therefore potentially increasing risk of lumbar spine injury under load (Cholewicki et al, 2005;Dankaerts et al, 2006;Mitchell et al, 2008). To date, no research has investigated the proximity of gymnasts landing postures to their end-range lumbar spine position.…”
mentioning
confidence: 99%